The Influence of Ice Structure upon Its Strength (Vliyanie Struktury lda na Ego Prochnost) - Lavrov,V. V. (1972)
The mechanical properties of ice depend upon the composition of the ice, on its structure. The degree of this dependence, however, is unknown, since little research on this question has been done. The results of laboratory experiments conducted by the author are reported in the present article. (Author) Draft trans. of Problemy Arktiki i Antarktiki (USSR) v20 p61-67 1965.